Investigating the Utilization of the Song 'Darl+ing' by Seventeen K-Pop Group in Improving English Grammar Skill - Riadil, Ikrar Genidal; Chonpracha, Pitchaya; Bujana, Novian Gilang; Nuswantoro, Aqila Gema (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Utilizing song as a medium for English language acquisition has emerged as a captivating and enjoyable approach incorporated within the curricula of Junior High School and Senior High School under the 2013 educational framework. This research aims to employ the song "Darl+ing" by Seventeen as a catalyst to reinforce and validate grammatical concepts. Through an intricate analysis of the song's lyrical content, this study endeavors to address two pivotal research inquiries: (1) the delineation of distinct grammatical structures presents within Seventeen's composition "Darl+ing" and (2) an exploration of students' perspectives about the integration of English songs for grammar instruction. Employing a qualitative research methodology, the data for this study was gathered from Senior High School students. Notably, 76% of respondents acknowledged the efficacy of employing the song's lyrics as an engaging pedagogical tool. In this model, the application of "Darl+ing" as an educational stimulus holds the potential to invigorate students' grammar learning experiences. The findings culminate in the observation that Seventeen's song encapsulates diverse grammatical elements, rendering it a captivating subject of study. Hence, leveraging song lyrics as a creative conduit serves as a source of inspiration, fostering students' grammatical proficiency and imbuing the learning process with a sense of enthusiasm. In essence, the researchers underscore the recommendation of song lyrics as an innovative strategy to facilitate a comprehensive grasp of grammatical nuances, particularly within the purview of tense variations